A fast response high voltage measuring system based on saline solution - Phoaphan, Busayapol; Triruttapiruk, Nawakun; Yutthagowith, Peerawut (My University, 2014)
This paper presents design and construction of a simple structure voltage measuring system with high energy absorption capability and fast response for measurement of nanosecond pulse voltage. The measuring system is composed of a high voltage divider and an attenuator. The high voltage part of the divider was constructed from saline solution contained in a plastic tube. The low voltage part of the divider and also the attenuator were constructed from metal film resistors enclosed in an aluminium housing. The voltage rating is 300 kV and the high voltage resistance is 11 kΩ. The developed measuring system has been tested according to the standard of IEC 60060-2 composing of a scale factor test, a withstand voltage test, a short term stability test. From the experimental results, the developed measuring system has good performance in measurement of the steep front voltage according to the standard of IEC 61211. From the unit step response test, the partial response time of the measuring system is less than 3 ns, the over shoot is 36%, and settling time is less than 150 ns. This accomplishment will be advantage for increasing capability of HV laboratory and for researches being about effect of fast transient voltage in transmission and distribution systems in Thailand.
Keywords: Resistive voltage divider; Response time; Saline solution; Steep front voltage; Unit step response